2011
DOI: 10.4103/0019-5413.87131
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of ultrasonographic measurements in suspected patients of developmental dysplasia of the hip and correlation with the acetabular index

Abstract: Background:Ultrasonography is accepted as a useful imaging modality in the early detection of developmental dysplasia of the hip (DDH). Early detection and early treatment of DDH prevents hip dislocation and related physical, social, economic, and psychological problems. The purpose of this study was to evaluate the reliability of ultrasonographic and roentgenographic measurements measured by seven different observers.Materials and Methods:The alpha angles of 66 hips in 33 patients were measured using the Graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…All the individual US parameters evaluated in the first 3 months of life also showed close correlations with the overall radiographic parameters evaluated at 1 year of life. This finding is similar to those of many other studies, which also identified a close correlation between US and radiographic findings [10][11][12][13][14]17].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…All the individual US parameters evaluated in the first 3 months of life also showed close correlations with the overall radiographic parameters evaluated at 1 year of life. This finding is similar to those of many other studies, which also identified a close correlation between US and radiographic findings [10][11][12][13][14]17].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have suggested high rates of false positives, and that a significant proportion of cases of "ultrasoundpositive DDH" may spontaneously resolve without treatment [25,27,28]. Additionally, missed or late presentations of DDH were still prevalent despite US screening [10,17]. The current literature, therefore, contains varying opinions on the correlation between US and subsequent radiographic findings for patients with DDH, with some studies concluding that there was no significant positive correlation between the two [10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations